The relationship between perception and preventive health behaviors on the Coronavirus disease 2019 of diabetic mellitus patients in communities - Muangma, Suradet; Chaisombut, Donnapa (Journal of Nursing and Health Research, 2023)
Diabetic mellitus patient is a high-risk group, if infected with Coronavirus 2019. As they have a high chance of severe infection and death compared to general patients due to low immunity. Therefore, preventive behaviors against Coronavirus disease 2019 are important. This descriptive correlational study aimed to test the relationship between perception and preventive behaviors on coronavirus disease 2019 of diabetes patients. Purposive sampling was used to recruit 91 patients who received medical treatment at Ban Tam Health Promoting Hospital, Phayao Province. The research instruments consisted of a questionnaire on perception regarding Coronavirus disease 2019 and preventive behaviors on Coronavirus Disease 2019. Those questionnaires were approved by three experts with its content validity index value were between .67-1.00 and the Cronbach’s alpha coefficients were .90 and .90 respectively. Data were analyzed using descriptive statistics and Pearson’s correlation was used to test the relationship between perception and preventive behaviors. The results revealed that participants had a good perception on the Coronavirus disease 2019. When considering each component, it found that perceived susceptibility and perceived severity against Coronavirus disease 2019 were at a good level. However, perceived benefits and perceived barriers to Coronavirus disease 2019 were at a moderate level. The participants had a good level of preventive behaviors towards coronavirus disease 2019. Also, their perception was statistically related to the preventive health behaviors at moderate level (r=0.634). Research finding suggests that perception on Coronavirus disease 2019 should be promoted among diabetic patients living the community in order to have good preventive health behaviors on Coronavirus disease 2019.